THE DUTY TO TAKE CARE AND LIABILITY FOR THE ACT OF THE THINGS IN COMPARATIVE LAW - Díaz, Julio Alberto (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2013)
The twentieth century was extremely rich when referring to the formation of the fundamental bases for liability in both, Civil and Common Law. The present article aims at comparing different solutions for the same problem analyzing three of the most representative cases of that century in each system: Winterbottom v. Wright in England and the Arrêt Teffaine and the Jand’heur case in France.